The Rapes of Polish Women by Red Army Soldiers in 1945 in the Pomeranian Voivodeship - Ławniczak, Remigiusz (Instytut Historii Polskiej Akademii Nauk, 2024)
In January 1945, the Red Army launched an offensive and entered the future Pomeranian Voivodeship, encompassing Pomerania and Kuyavia territories. There have been publications presenting the end of the German occupation and the installation of the communist regime. What is missing, however, is a study discussing the crimes, including rapes and common offences committed by Red Army soldiers in the voivodeship. The author has attempted to determine whether it is possible to differentiate the nationality of the rape victims and to describe the Soviet soldiers’ sexual violence against Polish women. The author’s analysis also tackles questions about the scale of the phenomenon and the motives of the rape perpetrators. The analysis is based mainly on archival material, memoirs, and Polish and foreign literature.
p. 85-129
Keywords: Red Army; Pomerania; Pomerania (Poland; region) - 1939-1945 (War and Occupation); Kuyavia; Second World War; 1945; sexual violence; rape as a weapon of war